Management of Nabi Nuh AS (Study of Business Strategic Planning in dealing with risks, crises and disasters in an Islamic approach: the COVID-19 pandemic crisis as a model (qualitative study using grounded theory) - Amalia, Alfi; Andrew Satria Lubis (Journal Of Management Analytical and Solution (JoMAS), 2023)
The current study seeks to produce a theory of business management strategy data in times of crisis in Islam which refers to the story of Prophet Noah AS, also aims to identify the strategies used by business leaders in the crisis management process. A grounded theory approach is applied which is one of the qualitative designs. Fill in the verses of the Qur'an and hadith related to the problems and crises being analyzed.The results of a qualitative analysis of the verses of the Qur'an and the noble hadith of the Prophet's sunnah have resulted in four concepts which constitute a broad conceptual theory of crisis management strategies according to an Islamic approach. These concepts are: Crisis management strategies in Islam, stages of crisis management strategies, characteristics of leaders who manage crises, and the role of a leader during the crisis management process. These results have wide application in the field of leader training, and also recommend future studies to verify theoretical assumptions emerging from the data in this study about crisis management strategies in Islam (COVID-19 pandemic crisis as model).